2012
DOI: 10.5414/np300510
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell glioblastoma with unique bilateral cerebellopontine angle localization considered as extraaxial tumor growth in a patient with neurofibromatosis Type 1

Abstract: Giant cell glioblastoma multiforme (GCGBM) is a rare variant of glioblastoma, occurring predominantly in the cerebral hemispheres. Its infratentorial localization has been documented occasionally, while GCGBM in the cerebellopontine angle (CPA) region has not been described so far. We report a case of GCGBM presenting primarily as an extraaxial bilateral CPA tumor in a 29-year-old woman with neurofibromatosis Type 1 (NF1). The patient died shortly after surgery of the right CPA tumor. Postmortem study of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Molecular profiling of the CPA glioblastoma has revealed underlying genetic mutations in the TP53, TERT, NF1, and RB1 genes 11 . Taraszewska et al 12 reported bilateral CPA glioblastoma in a patient with neurofibromatosis type 1, suggesting a possible genetic link. The mean age in our cohort was lower when compared with the reported age in the literature, with a slight male predominance, usually observed in glioblastomas 1,7 .…”
Section: Discussionmentioning
confidence: 99%
“…Molecular profiling of the CPA glioblastoma has revealed underlying genetic mutations in the TP53, TERT, NF1, and RB1 genes 11 . Taraszewska et al 12 reported bilateral CPA glioblastoma in a patient with neurofibromatosis type 1, suggesting a possible genetic link. The mean age in our cohort was lower when compared with the reported age in the literature, with a slight male predominance, usually observed in glioblastomas 1,7 .…”
Section: Discussionmentioning
confidence: 99%
“…The first case was reported by Kroh et al in 2004 in an 8-year-old child, [3] and the second case was reported by Taraszewska et al in a 29-year-old female in 2013. [4] Histopathologically, GCGs correspond to WHO Grade IV.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the third case report of GCG associated with clinical features of NF, and the second case report in a child in a scenario of NF type 1 (NF1). [3,4] In this case report, we discuss GCG with a review of the relevant literature.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Such a radiologic finding is exceedingly rare in giant cell glioblastoma, with only 2 cases recently described in the English medical literature. 4,5 Such a diagnosis, erroneously suspected, could have entailed in inadequate therapy; that is why we want to stress the importance of combined application of multiple MRI techniques including routine sequences and MR spectroscopy, diffusion and perfusion as a preferred policy in the exploration of brain tumors and assessment of differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%